A conveniência da implementação da Diretiva Quadro da Água no ordenamento jurídico brasileiro como medida efetiva de justiça ambiental: o caso da exploração do Nióbio em Catalão - Branco Filho, Thelmo de Carvalho Teixeira (2017)
This thesis will address the convenience of implementing the Water Framework Directive (WFD) in the Brazilian legal system, as a measure of effective environmental justice. In line with the focus of this investigation, it is also considered damages, benefits and conflicts that take place in the Municipality of Catalão, State of Goiás, Brazil, where Niobium is extracted. One of the major sources of conflict therein is water, since the extraction of minerals causes the silting of springs, among other problems. This study has the purpose of contributing to the improvement of the regulation and effectiveness of environmental protection, departing from a popular conflict, which basically involves water. This research leads us to contemplate how the pressure related to social conflicts in Catalao has helped to redefine protection strategies that would secure greater effectiveness of environmental laws. The research hypothesis will be grounded on legal and other scientific theories, including environmental, social and legal diagnoses, which ensure the interdisciplinary nature of the study. The methods employed were the case study and the inductive method, since this research relies on specific data on mining exploration in the Municipality of Catalão, although aiming at looking for premises that could be applied wherever this type of activity may occur. We are seeking answers to "how" and/or "why" the social phenomena combined with the legal one are operating. Mineral resources are the passion of the 21st century, since they are closely associated with the technological age and exacerbated consumption. This fact should be observed with caution, since there is a need for concern with future generations, since those are non-renewable goods. The major challenge of the WFD is the access to information, transparency and participation of citizens as well as all stakeholders in the various stages of the decision-making process, as well as the control on diffuse emissions based on best environmental practices, which in Brazil leave to be desired. Consequently, the existence of this tool in national territory will strengthen other institutes such as environmental responsibility, environmental licensing and the use of best available techniques